A Descriptive Study to Assess Knowledge, Attitude and Practices of Mothers Regarding Prevention of Juvenile Sexual Abuse (Medico Legal Update, 2020)
Sexual assault involves a perpetrator coercing or physically forcing a sexual act or non-consensual touching. Adescriptive study was conducted to assess knowledge, attitude and practices of mothers regarding preventionof juvenile sexual abuse in selected community area in Kanchipuram (DT), Tamil Nadu. Objectives were toassess the knowledge, attitude and practices of mothers regarding the prevention of juvenile sexual abuse andto find out association between the knowledge, attitude and practices of mothers regarding juvenile sexualabuse and selected demographic variables. Mothers occupation had significant association with knowledgeregarding prevention of juvenile sexual abuse (p=.030). Majority of the samples had adequate knowledge(80.0%), adequate attitude (62.2%) and adequate practice (75.6%) regarding prevention of juvenile sexualabuse.